Preparation and Characterization of a Novel Activated Carbon from Vine Shoots by ZnCl2 Activation and Investigation of Its Rifampicine Removal Capability - Erdem, Mehmet; Orhan, Ramazan; Sahin, Mehmet; Aydin, Ekrem (Springer International Publishing Ag, 2016)
Preparation and characterization of a novel activated carbon obtained from vine shoots by ZnCl2 activation and its rifampicine removal capacity were investigated in this study. The effects of activation temperature and impregnation ratio (precursor/ZnCl2) on the activated carbon properties were investigated. The prepared activated carbon was characterized by BET surface area, surface functional group analysis by Boehm's titration and FT-IR analysis, pH(pzc), iodine number, SEM-EDX, and particle size distribution. The results showed that the surface area, pore size, and pore volume of the activated carbon increased with the increasing temperature and impregnation ratio and reached maxima at the impregnation ratio of 40/30 at 700 degrees C. Under the optimal conditions, it was determined that the BET surface area, total pore volume, iodine number, and pH(pzc) of the activated carbon were 1689 m(2)/g, 0.842 cm(3)/g, 1276 mg/g, and 4.8, respectively, and it has mainly acidic functional groups (total 0.2516 meq/g) on its surface. The activated carbon obtained was evaluated for rifampicine removal efficiency depending on contact time, adsorbent dosage, and initial concentration of rifampicine. Maximum adsorption capacity of rifampicine by the activated carbon (Q degrees) was determined according to Langmuir adsorption isotherm. The adsorption data was best fitted to the Langmuir isotherm with R-2 of 0.983 and Q degrees was found to be 476.2 mg/g.
Keywords: Activated carbon; Vine shoots; Activation; Zinc chloride; Rifampicine